Legal Review of the Existence of Customary Land of the Sakai Tribe in Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency Based on the Basic Agrarian Law - Ulva Dina; Moza Dela Fudika; Ellydar Chaidir; Desi Apriani; Asri Muhammad Saleh; Syafrinaldi Syafrinaldi; Sri Murtini (Proceeding International Conference on Malay Identity, 2021)
Abstract The problem of land ownership in Indonesia in general and in the Kesumbo Ampai Village area has complex problems. Among them, the government takes over land from the people, to be developed in accordance with the plans that have been set to continue economic modernization or the creation of oil palm fields for investors, both inside and outside the State. This land problem shows a conflict of interest between the government, which sees land as capital for national development, and local residents who see land as a source of income. Based on the above problems, the formulation of the problem is how is the legal review of the existence of customary land in the Sakai Tribe Village based on the UUPA. The research method uses observation research. The result of the research is that the existence of the Sakai tribe community has been based on the conditions of existence determined by law so that the Sakai tribe is still truly a customary law community, as well as the land or land on which they live is land belonging to their ancestors for generations which is still jointly owned, which in terms of management and control and use of the land still follows the rules of customary law that apply in their environment, supervised by the customary leader they have.